Ultrafast imaging of isolated molecules with electron diffraction. (22nd February 2016) - Centurion, Martin
Abstract: Recent advances in ultrafast electron diffraction offer the possibility to image isolated molecules with sub-Angstrom spatial resolution in ultrafast time scales. In particular, diffraction from aligned molecules has opened the door to retrieving three-dimensional structures directly from experimental data. In this manuscript we review the progress in ultrafast gas electron diffraction and discuss remaining challenges to achieve a temporal resolution of sub-100 fs, which is needed to observe the nuclear motion in chemical reactions in the gas phase.